Interdependent Group Contingencies Decrease Adolescents' Disruptive Behaviors During Group Therapy: A Practitioner's Demonstration. (May 2017) - Brogan, Kristen M.; Falligant, John Michael; Rapp, John T.
Adolescents who have been adjudicated for illegal sexual behavior may receive treatment that requires attending group therapy sessions and classes. For some adolescents, nonsexual problem behavior (e.g., verbal outbursts, noncompliance) interferes with their ability to participate in group treatment. Researchers used a multiple-baseline across groups design with an embedded changing criterion design to evaluate the effects of an interdependent group contingency for decreasing disruptive behavior in adolescents across two therapy groups. Results indicated that the procedure was effective in reducing disruptive behavior emitted by adolescents in group therapy. Measures of social validity indicated that both the therapists and students viewed the overall procedures and outcomes as acceptable. Implications for interdependent group contingencies across diverse populations are discussed.